Impacto do treinamento físico na dor de pacientes com câncer de mama - Reis, Andréa Dias (2016)
Introduction. The pain is one of the most prevalent adverse effects in patients with breast cancer, but an ideal physical training protocol for the treatment of pain in patients with breast cancer is not yes defined. Objective. Evaluate the effects of combined training in pain, fatigue, maximum oxygen volume (VO2max), body mass index (BMI), flexibility and strength in patients with breast cancer. Methods. Pilot controlled study with 28 patients in chemotherapy, radiation therapy and clinical follow-up in a reference center, aged 30 to 59 years old, not practicing physical training in the last three months. The Experimental Group (EG) was submitted in 12 weeks to 3 sessions per week of aerobic and resistance training, with 60 minutes duration and 2 sessions per week of flexibility training, each flexibility exercise lasting 20 seconds in 3 series. The Control Group (CG) only conducted the conventional hospital treatment. All evaluations were performed at baseline and after 12 weeks. Results. The patients of EG showed a reduction in total pain points (p=0,0047), in pain intensity (p=0,0082) and in pain interference in the lives (p=0,0201). Had an increase VO2max (p=0,0001), in flexibility (p=0,0001) and in strength on both sides (right p=0,0001 and left p=0,0008). No differences were observed in fatigue (p=0,0953) and BMI (p=0,6088). The CG remained unchanged in all variables. Conclusion. The combined training was effective in reducing pain, and increased VO2max, flexibility and static strength in patients with breast cancer.